Changes in Wetu Telu Islamic Traditions in the Community of Narmada District, West Lombok Regency from 1998 to 2022 - Ibrahim, Alfin Malik; Thohri, Muhammad; Maharsi, Maharsi (Sabda: Jurnal Kajian Kebudayaan, 2024)
This study examines the changes in the Wetu Telu Islamic tradition in Narmada District, West Lombok Regency from 1998 to 2022. Wetu Telu Islam is a tradition practiced by some Sasak people, combining animistic beliefs and ancestral worship with Islamic teachings. In contrast, Waktu Lima Islam follows Shari’ah more comprehensively as taught by the Qur’an and Hadith. The rapid advancement of information technology, particularly social media, has influenced religious behavior among the Wetu Telu community. This research is descriptive-qualitative, using an anthropological approach to religion and employing historical research methods, including heuristics, verification, interpretation, and historiography. The findings indicate that: first, the social structure in West Lombok features stratification affecting political, traditional, and religious dominance. Second, Wetu Telu Islam represents a syncretism of Islamic, Hindu, and animistic teachings, creating a new culture while maintaining Islamic values. Third, the Wetu Telu tradition has undergone changes due to advances in knowledge, technology, and shifts in societal perspectives.